An examination of police cadets’ perceptions of corruption - Cetinkaya, Nebi (International journal of police science & management, 2020)
The purpose of this paper is to examine police cadets’ perceptions of the seriousness of police corruption. This study attempts to explore and delineate a variety of factors that may influence police cadets’ perceptions about some basic types of corruption. A comparison between future supervisors’ and line officers’ perceptions of specific aspects of corruption is lacking. A quantitative research design was used for data collection. The results of this study indicated that there were significant differences in police cadets’ perceptions of the seriousness of corruption based on their parents’ education level, occupation, and income. In addition, the findings revealed that cadets’ sociodemographic background, such as parents’ education level and type of occupation, as well as the cadet’s organizational affiliations, such as their respective police training school, had significant effects on their perceptions of seriousness involving corruption scenarios. This study provided important and useful information for policy-makers and leadership cadres responsible for police training.